Optimalisasi Kemasan Produk UMKM untuk Meningkatkan Nilai Jual dan Daya Saing di Pasar Lokal Medan Johor - Adrianto, Adrianto; Lubis, Dewi Shinta Wulandari (Jurnal Pengabdian Masyarakat Inovasi, 2025)
This community service activity aims to increase the competitiveness and sales value of Micro, Small, and Medium Enterprises (MSMEs) products through product packaging optimization. The program focused on MSMEs in the Medan Johor area, who still face various challenges in terms of design, materials, and information on product packaging. Implementation methods included outreach, training, and technical assistance to MSMEs in designing and implementing more attractive, informative, and market-standard packaging. The results of the program demonstrated an increased understanding of the importance of packaging among MSMEs, as well as tangible changes in product packaging design that have increased consumer appeal and product sales value in the local market. This program is expected to become a model for MSME empowerment that is applicable and sustainable.